Updating Potential Soft Skills For Telecommuters In A Home-Work Double Situations In The Covid 19 Pandemic - Hesty Prima Rini; Dewi Khrisna Sawitri (Ilomata International Journal of Social Science, 2021)
Telecommuting is used to work far from the central office to achieve performance but now the term is shifting. Work from home is now hard to do since workers also have to take care of their families. Job routines are still demanding and at the same time, taking care of family and handling domestic affairs tasks can not be neglected since safety comes first to protect the family from the virus. Job demands shift in this COVID 19 pandemic as many domestic and office problems occur while people work from home. This review paper elaborates the important soft skills for telecommuting who work from home in this pandemic. The review was conducted from 1986 until the latest one in 2020. This review results in some soft skills that have evidenced their presence for telecommuters. The existence of soft skills are demanding and undoubtedly plays important role in helping telecommuters complete their job.